2001
DOI: 10.1034/j.1600-0528.2001.290406.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral melanin pigmentation related to smoking in a Turkish population

Abstract: The results of our study show that smokers in a Turkish population had significantly more pigmented oral surfaces than nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…3,4,6 Several therapeutic techniques have been proposed and employed for gingival depigmentation. Some of them, such as chemical techniques, are no longer used, 7 but some others such as gingival abrasion are still practiced.…”
Section: Comparison Of Gingival Depigmentation Efficacy Of Two Differmentioning
confidence: 99%
“…3,4,6 Several therapeutic techniques have been proposed and employed for gingival depigmentation. Some of them, such as chemical techniques, are no longer used, 7 but some others such as gingival abrasion are still practiced.…”
Section: Comparison Of Gingival Depigmentation Efficacy Of Two Differmentioning
confidence: 99%
“…6) [104]. Recently it was shown that smokers in a Turkish population had significantly more pigmented oral surfaces than non-smokers [105]. The changes are symptomless, it is not premalignant, and it seems that the pigmentation is reversible upon smoking cessation [104,106].…”
Section: Smoker's Melanosis and Hairy Tonguementioning
confidence: 99%
“…El estudio de Espinoza et al determinó la prevalencia de las lesiones pigmentadas en un 2,8%; el estudio de Axéll también las agrupa y señala una prevalencia de un 9,94%. Los valores obtenidos en nuestra muestra se asociarían al alto número de población indígena en nuestra región, siendo un factor relevante señalado en los textos de referencia como un antecedente de riesgo para la presencia de algunos tipos de lesiones de este grupo de patologías (Unsal et al, 2001).…”
Section: Discussionunclassified